2018
DOI: 10.1111/jocn.14069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nurse‐led clinical pathway in coronary artery bypass graft surgery: A quasi‐experimental study

Abstract: This study contributes to previous studies supporting clinical pathway use can improve the length of stay and quality of care in patients undergoing coronary artery bypass graft surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…First of all, a randomized control trial consisting of 188 patients at a tertiary center in the United Kingdom evaluating a nurse-led support and educational program for patients who are waiting for CABG showed that the patients were very satisfied and appreciated support of the nursing staffs but communication among staffs and with the patients were suggested to be improved since patients’ appreciate physical and psychological preparations prior to surgery [ 21 ]. In a prospective study consisting of patients who were hospitalized for CABG between April 2014 and November 2015, in a hospital in Turkey, the authors demonstrated that the nurse-led clinical pathway was associated with an improvement in the length of hospital stay, that is, patients could be discharged earlier after the open heart surgery, and a significantly lower rate of complications was reported among the participants who were assigned to the nurse-led treatment group showing a benefit of nurse-led intervention following CABG [ 22 ]. Another study evaluated the safety and efficacy of a nurse-led clinic for patients who were recovering after CABG [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, a randomized control trial consisting of 188 patients at a tertiary center in the United Kingdom evaluating a nurse-led support and educational program for patients who are waiting for CABG showed that the patients were very satisfied and appreciated support of the nursing staffs but communication among staffs and with the patients were suggested to be improved since patients’ appreciate physical and psychological preparations prior to surgery [ 21 ]. In a prospective study consisting of patients who were hospitalized for CABG between April 2014 and November 2015, in a hospital in Turkey, the authors demonstrated that the nurse-led clinical pathway was associated with an improvement in the length of hospital stay, that is, patients could be discharged earlier after the open heart surgery, and a significantly lower rate of complications was reported among the participants who were assigned to the nurse-led treatment group showing a benefit of nurse-led intervention following CABG [ 22 ]. Another study evaluated the safety and efficacy of a nurse-led clinic for patients who were recovering after CABG [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Frailty-specific care pathways could identify vulnerable patients and ensure they have the best opportunity for recovery. 27,28 Although frailty-specific pathways already exist for many noncardiac surgical interventions (e.g., colorectal procedures, 29 and hip and knee arthroplasty 30 ) cardiac surgical services have largely focused on postoperative targets (e.g., early extubation and mobilization 31 ) to reduce duration of CVICU and subsequent acute hospital stay. A recent study described a comprehensive perioperative pathway for enhanced recovery after cardiac surgery targeting all nonemergency adult patients; however, this study did not specifically address what may be unique domains related to frailty (e.g., cognitive [delirium], physical strength [sarcopenia], mobilization [slow gait speed], polypharmacy and susceptibility to adverse effects).…”
Section: Discussionmentioning
confidence: 99%
“…CABG has shown long-lasting benefits compared to angioplasty. Surgical techniques have been standardized since the 1960s, post-operative protocols have been improved, and effective post-operative care has been developed (16). However, coronary artery disease is the leading cause of death and illness in the world.…”
Section: Discussionmentioning
confidence: 99%